2019
DOI: 10.1155/2019/4914631
|View full text |Cite
|
Sign up to set email alerts
|

Polymyositis-Dermatomyositis and Interstitial Lung Disease in Pregnant Woman Successfully Treated with Cyclosporine and Tapered Steroid Therapy

Abstract: Polymyositis-dermatomyositis is extremely rare during pregnancy, and immunosuppressive therapy should be administered after carefully considering the effects on both the mother and fetus. Several reports have associated the disease activity with fetal prognosis, higher rates of eclampsia, preterm births, and fetal deaths. We report our experience with a patient who was diagnosed with polymyositis-dermatomyositis complicated by interstitial lung disease during pregnancy and was treated with a combination-immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Examples of clinical case studies for treating pregnant patients with DM or PM, especially CADM, are relatively rare, and case studies of a similar nature that we were able to identify are shown in supplementary material (18,(26)(27)(28). Tomohiro et al (18).…”
Section: Discussionmentioning
confidence: 79%
“…Examples of clinical case studies for treating pregnant patients with DM or PM, especially CADM, are relatively rare, and case studies of a similar nature that we were able to identify are shown in supplementary material (18,(26)(27)(28). Tomohiro et al (18).…”
Section: Discussionmentioning
confidence: 79%
“…4 Only 2 of 68 pregnancies (2.94%) after DM/PM onset were complicated by hypertension 6 . The most frequently mentioned complication of DM/PM was interstitial lung disease 19–23 . The rate of cesarean delivery ranged from 23.3% 6 to 88.2% 5 (Supplementary Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…6 The most frequently mentioned complication of DM/PM was interstitial lung disease. [19][20][21][22][23] The rate of cesarean delivery ranged from 23.3% 6 to 88.2% 5 (Supplementary Tables S1 and S2).…”
Section: Pregnancy In Dm/pmmentioning
confidence: 99%
“…Immunosuppressants are chosen in patients with DM who are resistant to GC therapy (recommendation grade: B) [3]. Choice of immunosuppressant can be among MTX (7.5-15 mg/week), azathioprine (AZA, 50-100 mg/ day) [6], tacrolimus (Tac, trough concentration 5-10 ng/ml or 0.075 mg/kg/day) [26], cyclosporin A (CsA, 4-6 mg/kg/day) [27], mycophenolate mofetil (MMF, 1-3 g/day) [3] and cyclophosphamide (CPA, 50-100 mg/day) [28]. Combination of GC and immunosuppressants is chosen with the objective of [3], especially utilized as therapy for dysphagia (evidence level: V, recommendation grade: C1) [3,30].…”
Section: Medical Managementmentioning
confidence: 99%